Centering trauma‐informed approaches in schools within a social justice framework. Issue 12 (12th February 2022) - Davis, Whitney; Petrovic, Lea; Whalen, Kathleen; Danna, Laura; Zeigler, Karaline; Brewton, Avery; Joseph, Maureen; Baker, Courtney N.; Overstreet, Stacy; ,
Abstract: Growing evidence establishing the prevalence and educational consequences of childhood trauma has led to a national focus on equipping schools to support the specific needs of students who have experienced trauma. Despite clear evidence of disproportionate trauma exposure among students of color, most models of trauma‐informed schools do not explicitly address the intersection of race and trauma within their system‐level efforts to help staff realize the prevalence and impact of trauma, recognize the signs of trauma exposure, or respond in ways to avoid retraumatization. This manuscript will review existing efforts to integrate a social justice focus within our ongoing work as part of the Safe Schools NOLA project. We present our conceptual framework and describe how principles relevant to social justice are intentionally integrated into strategies that support the adoption and implementation of trauma‐informed approaches in schools. We also discuss limitations in our current approach and offer suggestions to support the development of trauma‐informed schools that can advance a social justice agenda. HIGHLIGHTS: Recognizes the role of discriminatory and oppressive historical and societal factors in creating safe and equitable school environments. Provides a conceptual framework for integrating social justice and trauma‐informed approaches in schools. Identifies existing and developing practical resources that may be used to advance a social justice agenda within trauma‐informed schools frameworks.